Identifikasi Jamur Dermatofita Penyebab Tinea unguium Pada Kuku kaki Petani di Dusun Ballakale Desa Aska Kecamatan Sinjai selatan Kabupaten Sinjai: Identifikasi Jamur Dermatofita Penyebab Tinea unguium Pada Kuku kaki Petani di Dusun Ballakale Desa Aska Kecamatan Sinjai selatan Kabupaten Sinjai - Nurfadillah, Hartati, Sulfiani (Kampurui Jurnal Kesehatan Masyarakat, 2021)
Tinea unguium is an infection of the nail plate caused by the fungus Dermatophyta. Themajority of the livelihood in Dusun Ballakale Desa Aska Kecamatan Sinjai selatan Kabupaten Sinjai is farming where the habit of farmers in this area is to work on rice fields that are in direct contact with soil, water and mud for a long time without wearing protective equipment, one of which is boots to protect the feet. Nails that are in direct contact with soil or mud for a long time and are rarely cleaned can trigger fungal growth. The purpose of this study was to determine the presence or absence of a dermatophyte fungus that causes tinea unguium on farmers' toenails and to determine the type of dermatophyte fungus that causes tinea unguium on farmers' toenails. The research method used is categorical descriptive with 10 samples examined. Meanwhile, the examination method in this research is using direct microscopic method with KOH 20 % and culture using Sabouraud Dextrose Agar (SDA) media. The results of the direct examination with KOH 20 % obtained 2 positive samples with the discovery of hyphae. And the results of the culture examination showed dermatophyte fungi in 5 samples of the Trichophyton rubrum type melanoid, Microsporum audouinii, and Epidermophyton floccosum, 3 samples of the non-dermatophyte fungus Aspergillus flavus, and 2 samples were not identified.